Factors Influencing Ownership Pattern and its Impact on Corporate Performance of Selected Indian Companies - Janaki S; Dr. P.G. Thirumagal (International Journal of Engineering and Management Research, 2022)
This study on factors influencing Ownership pattern and its impact on corporate performance has used five industries data viz Automobile industry, IT industry, Banking industry, Oil & Gas industry and pharmaceutical industry for five years from 2017 to 2021. First the factors influencing ownership pattern was identified and later its impact on corporate performance was analysed. Multiple Regression, ANOVA and Correlation was used in SPSS 28. Percentage of independent directors on the board and size of the company has significant impact on Indian Promotor holding and non-institutional ownership has significant impact on corporate performance.